Hubungan Asupan Zat Gizi Makro dan Pengetahuan Gizi Seimbang Dengan Status Gizi pada Siswa SMA Negeri 1 Tegineneng - Sari, Nurina; Nurhartanto, Adhi; Adyas, Atikah (Journal of Education Technology Information Social Sciences and Health, 2025)
According to 2018 Riskesdas, the prevalence of CED in adolescent girls aged 13-15 years reached 9.2% and in adolescent boys it was 8.7%. These figures show that SEZs are a problem that requires serious attention from various parties. This research was conducted in an analytical observational manner with a cross sectional design. The research population was all class X students of SMA N 1 Tegineneng with a sample of 100 people taken using simple random sampling. Macronutrient intake used a 3x24 hour food recall questionnaire and knowledge of balanced nutrition used a questionnaire in the form of 15 questions. Univariate and bivariate data analysis using the chi-square test. The results that there was a relationship between intake of macronutrients (carbohydrates) and nutritional status (p=0.001), there was a relationship between intake (protein) and nutritional status (p0.001) and there was a relationship between intake (fat) and nutritional status ( p=0.006), and there is a relationship between knowledge of balanced nutrition and nutritional status (p=0.009).